A Comparison of Folk Printmaking in China and the West - Wei Yuan (SHS Web of Conferences, 2024)
Chinese and Western popular printmaking art share common roots in primitive art. Deeply ingrained in the daily lives of the masses, Chinese and Western folk printmaking art, with its vibrant artistic energy, has become an integral part of people’s lives. This paper presents a comprehensive overview of popular printmaking in both regions, encompassing its history, representative works, and materials. The development of Chinese art can be broadly categorized into official art and folk art. Chinese popular printmaking art, as an art form directly derived from the people, possesses the characteristics of originality and authenticity. However, throughout Chinese art history, class status and artistic status were intertwined, leading to popular art being often as low-level and vulgar, rather than being recognized as art. In contrast, Western folk printmaking art did not harbor such hierarchical distinctions, instead directly acknowledging the originality and origins of art.